Pembuatan Website pada UMKM Triple’s Branded sebagai Media Promosi - Augustin Mustika Chairil; Elinawati Aisyah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The community service, especially for UMKM, in the form of creating a sales website aims to enhance the branding of Triple's Branded UMKM and assist UMKM in understanding the use and management of websites as a current promotional media. The creation of this website goes through three main stages carried out as part of this community service, including the preparation stage which involves field studies, needs analysis, and permits, then the second stage is the implementation and design of the website, and finally the evaluation stage. The community service in creating a website for UMKM has yielded results in increasing the knowledge and skills of Triple's Branded UMKM in managing and operating the website as a promotional medium by showcasing products aimed at increasing sales.